Community Empowerment in Strengthening the Sakinah Family: The Strategic Role of KUA in Bandar Lampung City - Faizal, Faizal; Khairullah, Khairullah (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
This study focuses on community empowerment efforts by the Office of Religious Affairs (KUA) in Bandar Lampung City in strengthening the sakinah family. This research uses a qualitative approach with field research methods, where data is collected through observation, in-depth interviews, and documentation. The results of the study show that only the capacity building program for couples through premarital courses (Suscatin) has been successfully implemented, while the youth education and economic empowerment program through the Sakinah Family Center (PUSAKA Sakinah) has not continued. The main obstacles identified include limited facilitators, inadequate infrastructure, and regulatory changes and political influence. However, positive responses from participants, professional facilitator competence, and collaboration between government agencies supported the success of the program. This research contributes to the understanding of the unique integration between religious, social, and economic factors in achieving a healthy family structure. Further research can examine the strategic role of KUA in empowering adolescents in the school environment.